Keefektifan Sense of Humor sebagai Media Dakwah - Hisny Fajrussalam; Ai Siti Nuratilah; Amelia Putri Cahyani; Maylan Nada; Moch Deannandra Fazrian (FONDATIA, 2022)
In preaching, using humor inserts in Islamic communication is something often practiced by some preachers. Humor aims to attract the attention of da'wah listeners and the part that listeners look forward to even though humor is only a complement an Islamic communication. However, the use of humor in da'wah sometimes becomes a boomerang for preachers who don’t pay attention to ethical boundaries and the provisions of applicable norms. So from the results of the author's analysis that the use of humor in Islamic communication is allowed to be a good way as long as the preacher pays attention that in inserting his humor he doesn’t forget the courtesy stipulated in the Hadith & Qur'an. Due to technological advances in preaching, at this time preachers and listeners don’t need to meet in person in one place, but with technological advances, there are a lot of media that can be used in online preaching on social media. In this study, we used quantitative methods by using data collection techniques in the form of surveys conducted online. From the survey, several respondents had different opinions, but 95% of them more often found and liked da'wah with humor inserts through the TikTok application.